A series of new microporous lanthanide frameworks [Ln(C8H3NO6)(L)0.5(H2O)]·3H2O (Ln = Pr, Nd, Sm and Gd, and L = C8H4O4or C8H4O4/C8H3NO6): Syntheses, characterization and photoluminescence properties - Kitt Panyarat (2018)
Four new microporous lanthanide coordination polymers of general formula [Ln(C 8 H 3 NO 6 )(L) 0.5 (H 2 O)]·3H 2 O (Ln = Pr, Nd, Sm and Gd, and L = C 8 H 4 O 4 or C 8 H 4 O 4 /C 8 H 3 NO 6 ) were hydrothermally synthesized using in situ ligand synthesis. The complexes are isostructural featuring the NbO type framework, which is constructed from chains of edge-sharing LnO 9 polyhedra. The one-dimensional channel extending in the [1 0 0] direction with an aperture of approximately 4 × 8 Å 2 houses water of crystallization, which are ordered in edge-shared pentagons by hydrogen bonding interactions. Evidence for the significance of the hydrogen bonding interactions in stabilizing the framework is presented. Crystallographic disorder in the organic ligands, including rare substitutional disorder, is described. The complexes show type I gas sorption isotherms characteristic of microporosity, and are thermally stable up to approximately 400 °C. The solid state luminescence properties of these complexes are included. © 2014 Elsevier Ltd. All rights reserved.